# Solve the following equations:

$\sqrt {2{x^2} + 5x - 7} + \sqrt {3\left( {{x^2} - 7x + 6} \right)} - \sqrt {7{x^2} - 6x - 1} = 0$

Last updated date: 16th Mar 2023

•

Total views: 306.6k

•

Views today: 4.85k

Answer

Verified

306.6k+ views

Hint: - Here, we just factorize the equation and take out common, to solve the equation.

$\sqrt {2{x^2} + 5x - 7} + \sqrt {3\left( {{x^2} - 7x + 6} \right)} - \sqrt {7{x^2} - 6x - 1} = 0$

We just factorize the equation which are under the root and write in its factor form as

$\sqrt {\left( {2x + 7} \right)\left( {x - 1} \right)} + \sqrt {3\left( {x - 1} \right)\left( {x - 6} \right)} + \sqrt {\left( {7x + 1} \right)\left( {x - 1} \right)} = 0$

And from here we take $\sqrt {\left( {x - 1} \right)} $ as common and write as

$\left( {\sqrt {\left( {x - 1} \right)} } \right)\left( {\sqrt {{\text{2x + 7}}} {\text{ + }}\sqrt {{\text{3}}\left( {{\text{x - 6}}} \right)} {\text{ - }}\sqrt {\left( {{\text{7x + 1}}} \right)} } \right) = 0$

By the above equation either $\sqrt {\left( {x - 1} \right)} = 0{\text{ }}$or $\left( {\sqrt {2x + 7} + \sqrt {3\left( {x - 6} \right)} - \sqrt {\left( {7x + 1} \right)} } \right) = 0$

If $\sqrt {\left( {x - 1} \right)} = 0{\text{ }}$then $x = 1$and

If $\left( {\sqrt {2x + 7} + \sqrt {3\left( {x - 6} \right)} - \sqrt {\left( {7x + 1} \right)} } \right) = 0$

We write it as

$\sqrt {2x + 7} + \sqrt {3\left( {x - 6} \right)} = \sqrt {\left( {7x + 1} \right)} $

On squaring we get

$2x + 7 + 3x - 18 + 2\sqrt {3\left( {2x + 7} \right)\left( {x - 6} \right)} = 7x + 1$

And by solving

$

2\sqrt {3\left( {2x + 7} \right)\left( {x - 6} \right)} = 2x + 12 \\

On squaring we get

3\left( {2x + 7} \right)\left( {x - 6} \right) = {\left( {x + 6} \right)^2} \\

6{x^2} - 15x - 126 = {x^2} + 36 + 12x \\

5{x^2} - 27x - 162 = 0 \\

5{x^2} - 45x + 18x - 162 = 0 \\

5x\left( {x - 9} \right) + 18\left( {x - 9} \right) = 0 \\

\left( {x - 9} \right)\left( {5x + 18} \right) = 0 \\

$

We get $x = 9$ and $x = \dfrac{{ - 18}}{5}$

$\therefore $ The values for $x$ are $1, 9$ and $\dfrac{{ - 18}}{5}$

Note:-Whenever such types of questions are given just try to factorize the equation to take out common from the roots to make the question easy to solve. And then solve the equation to find out the values.

$\sqrt {2{x^2} + 5x - 7} + \sqrt {3\left( {{x^2} - 7x + 6} \right)} - \sqrt {7{x^2} - 6x - 1} = 0$

We just factorize the equation which are under the root and write in its factor form as

$\sqrt {\left( {2x + 7} \right)\left( {x - 1} \right)} + \sqrt {3\left( {x - 1} \right)\left( {x - 6} \right)} + \sqrt {\left( {7x + 1} \right)\left( {x - 1} \right)} = 0$

And from here we take $\sqrt {\left( {x - 1} \right)} $ as common and write as

$\left( {\sqrt {\left( {x - 1} \right)} } \right)\left( {\sqrt {{\text{2x + 7}}} {\text{ + }}\sqrt {{\text{3}}\left( {{\text{x - 6}}} \right)} {\text{ - }}\sqrt {\left( {{\text{7x + 1}}} \right)} } \right) = 0$

By the above equation either $\sqrt {\left( {x - 1} \right)} = 0{\text{ }}$or $\left( {\sqrt {2x + 7} + \sqrt {3\left( {x - 6} \right)} - \sqrt {\left( {7x + 1} \right)} } \right) = 0$

If $\sqrt {\left( {x - 1} \right)} = 0{\text{ }}$then $x = 1$and

If $\left( {\sqrt {2x + 7} + \sqrt {3\left( {x - 6} \right)} - \sqrt {\left( {7x + 1} \right)} } \right) = 0$

We write it as

$\sqrt {2x + 7} + \sqrt {3\left( {x - 6} \right)} = \sqrt {\left( {7x + 1} \right)} $

On squaring we get

$2x + 7 + 3x - 18 + 2\sqrt {3\left( {2x + 7} \right)\left( {x - 6} \right)} = 7x + 1$

And by solving

$

2\sqrt {3\left( {2x + 7} \right)\left( {x - 6} \right)} = 2x + 12 \\

On squaring we get

3\left( {2x + 7} \right)\left( {x - 6} \right) = {\left( {x + 6} \right)^2} \\

6{x^2} - 15x - 126 = {x^2} + 36 + 12x \\

5{x^2} - 27x - 162 = 0 \\

5{x^2} - 45x + 18x - 162 = 0 \\

5x\left( {x - 9} \right) + 18\left( {x - 9} \right) = 0 \\

\left( {x - 9} \right)\left( {5x + 18} \right) = 0 \\

$

We get $x = 9$ and $x = \dfrac{{ - 18}}{5}$

$\therefore $ The values for $x$ are $1, 9$ and $\dfrac{{ - 18}}{5}$

Note:-Whenever such types of questions are given just try to factorize the equation to take out common from the roots to make the question easy to solve. And then solve the equation to find out the values.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE